DEVELOPMENT OF INDEPENDENT KNOWLEDGE ACTIVITIES OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS (Conference Zone, 2022)
The main task of Higher Education is the formation of the creative personality of a specialist capable of self-development, self-education and innovation. This problem is difficult to solve only by transferring from the teacher to the student in a ready-made form. It is necessary to transfer the reader from the consumer of passive knowledge to the creator of active knowledge, able to formulate the problem, analyze the ways of its solution, find the optimal result and prove its correctness. The current reform of higher education is inextricably linked with the transition from the paradigm of teaching to the paradigm of Education. In this article, opinions and comments are made on the development of independent cognitive activity of students of higher education institutions.